INVESTIGATIONS AT THE DARGAVS BURIAL GROUND IN PRIGORODNYI DISTRICT OF NORTH OSSETIA-ALANIA IN 2019 - Uspenskij, Pavel Sergeevic; Carikaeva, Zarina Hadzi-Muratovna (History, Archeology and Ethnography of the Caucasus, 2023)
The paper discusses the findings from the 2019 excavation conducted by the Institute of Archaeology of the Russian Academy of Sciences at the Dargavs catacomb burial ground, a reference necropolis associated with the medieval Alan culture. The research unveiled a previously unexplored two-level, three-chamber catacomb designated as No. 97 and 98, initially misinterpreted as two individual catacombs. The catacomb was situated in the central part of the burial ground. The catacomb’s inventory dates back to the second half of the 8th – mid-9th century. Interestingly, the multi-level catacombs, such as the one discovered, have not been documented in the archaeological records of this burial ground or in synchronous sites within the mountainous regions, including Chmi, Dagom, and others. The primary objective of this study is to introduce the collected materials and findings concerning the analysis of funerary practices and associated artifacts into the scholarly discourse. Standard archaeological research methods were employed in the execution of this work. The analysis of the burial complexes relied on the comparative typological method, along with a detailed examination of the stratigraphy and planigraphy of the excavated section. The proposed dating is confirmed by the results of radiocarbon dating, specifically from a sample collected from chamber No. 97. Within the burial complex’s chambers, both individual (specifically in catacomb No. 97) and collective burials (chambers 1 and 2 of catacomb No. 98) were revealed. The buried were accompanied by a diverse set of grave goods, including jewelry, amulets, mirrors, fibulae, an axe, a glass cup, and more. These artifact categories exhibit significant parallels with findings from sites associated with the Alan and nearest cultures of the Central Caucasus and the Middle Don. Through a comprehensive analysis, it was determined that chamber 1 of catacomb No. 98 was constructed first, followed by chamber 2 and catacomb No. 98. This study serves as a vital supplement to previously released publications on the results of natural science research, encompassing anthropological, paleozoological, palynological, and radiocarbon dating studies of catacomb materials.
Keywords: Central Caucasus; Dargavs burial ground; Alan culture; catacomb; 8-9th century